2022
DOI: 10.14202/vetworld.2022.919-924
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with tropical theileriosis in Egyptian dairy cattle

Abstract: Background and Aim: Theileria annulata is the most prevalent piroplasm infecting cattle across Egypt. Theileriosis is transmitted by ixodid ticks of the genus Hyalomma. This study aimed to estimate the prevalence of theileriosis in cattle and their associated risk factors for infection. Materials and Methods: A total of 570 blood samples were collected from cattle from five governorates (administrative districts) in Egypt and examined using a polymerase chain reaction assay to estimate the prevalence of tropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
2
12
2
Order By: Relevance
“…There was no statistical difference between infection prevalence in female and male cattle. This agrees with previous studies that showed that gender is not a risk factor for T. annulata infection in cattle maintained in endemic stability farms since the tick populations are sufficiently high to reach animals of both sexes (Flach et al., 1995; Gharbi et al., 2014; Selim et al., 2022). However, the difference between the sexes is observed for clinical cases, as females develop more frequently TT clinical cases than males.…”
Section: Discussionsupporting
confidence: 93%
“…There was no statistical difference between infection prevalence in female and male cattle. This agrees with previous studies that showed that gender is not a risk factor for T. annulata infection in cattle maintained in endemic stability farms since the tick populations are sufficiently high to reach animals of both sexes (Flach et al., 1995; Gharbi et al., 2014; Selim et al., 2022). However, the difference between the sexes is observed for clinical cases, as females develop more frequently TT clinical cases than males.…”
Section: Discussionsupporting
confidence: 93%
“…This finding could be attributed to the similar management practices that were followed for all animals regardless of their sex ( 26 , 55 ). Also, a recent study in Egypt reported no significant association between animal sex and Theileria infection ( 56 ). However, another study in China reported higher risk of infection in male cattle than females, but did not provide a clear explanation for this finding ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Theileriosis is distributed throughout the world, from Asia, the Middle East and South Europe to North Africa [ 38 , 39 ] and is transmitted by several types of hard (Ixodidae) ticks: Hyalomma anatolicum , Hyalomma lusitanicum, Hyalomma scupense , Hyalomma detritum detritum , and Hyalomma dromedarii [ 40 , 41 , 42 ]. According to some researchers, the prevalence of theileriosis in cattle in China was 39%, Iran 33%, India 31.7%, Pakistan 21.2%, Bangladesh 2.69% [ 42 ], and Egypt 16.49% [ 43 ].…”
Section: Discussionmentioning
confidence: 99%